Comparison of microbroth dilution and e-test methods for detecting Fosfomycin susceptibility in pseudomonas aeruginosa - Gongqing Song; Xiuzhen Xu (Journal of Global Antimicrobial Resistance, 2025)
Objectives: Pseudomonas aeruginosa’s susceptibility to fosfomycin was assessed using microbroth dilution (MBD) and E-test methods. The most reliable method was determined by comparing the results with those of the reference agar dilution (AD) method. Methods: A total of 62 P. aeruginosa isolates from 62 patients, comprising 29 carbapenem-resistant (CRPA) and 33 non-carbapenem-resistant (non-CRPA) strains, were collected. Drug susceptibility was assessed using the AD, MBD, and E-test methods. According to the recommendations of CLSI and EUCAST, using AD as a reference, the results were interpreted using 64 µg/mL as the breakpoint. The evaluation metrics included categorical agreement (CA), major error (ME; false-resistant), very major error (VME; false-susceptible), and Cohen’s kappa values. Results: The results indicated that the susceptibility of all three methods exceeded 85%, with both MIC50 and MIC90 values being ≥ 64 µg/mL, and no significant difference was observed among them. For different P. aeruginosa types, the E-test demonstrated substantial variability compared with the other two methods. Finally, the MBD and E-test were compared with AD, with VME and Cohen’s kappa values of 1.61%/6.5%, and 71.37%/28.4%, respectively. Conclusions: Fosfomycin demonstrated significant activity against P. aeruginosa. MBD is more suitable than the E-test for assessing the susceptibility of fosfomycin against P. aeruginosa. Based on our results, we firmly believe that the MBD method can serve as an alternative to the AD method for detecting CRPA.